Perception of feminine vulnerability to the virus of Aids in the family strategy health - Carneiro, Wendell S.; Rodrigues, Jailson Alberto; Felix, Micheline R.; Athayde, Ana Célia R.; Lôbo, Katiuscia M.S.; Vilela, Vinícius L.R. (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: starting from the decade of 1990, the profile of aids changed. The main transmission way started to be the heterosexual, which provoked a significant increase in the number of cases of the disease in women. Objective: before the diversity of factors that envolves the subject HIV/aids, appeared the necessity of the realization of a study about the perception of the women about their vulnerability to the virus, to identify taboos and myths envolved in the way of disease to be represented in the society. Methods: for that, a quantitative study was done in unity of health of the family (USF) of the local authority of Campina Grande - PB, with sample of 35 women of active sex life. Results: 80% of this women are married; 17,1% are single women and 2,9% are divorced; 37,1% have twelve or more complete years of study; 31,4% five to eight years of study; 22,9% from nine to eleven years of study and 8,6% from zero to four years of study; 57,1% do not practice religion; 65,7% did not use condom in it last intercourse; 37,2% considered impossible to acquire the HIV/aids; 25,7% considered almost impossible; 20% considered improbable and 17,1% of the women considered possibly. Conclusion: the interviewed do not have a good perception of their vulnerability to the HIV/aids, besides, the use of condom still is not a usual practice, even in women that frequent the services of health.